Addressing Health Disparities In Maternal and Child Health: A Community-Based Approach - Sarah Martinez; David Nelson (International Journal of Public Health, 2024)
This study investigates the effectiveness of community-based interventions in addressing health disparities in maternal and child health. By implementing programs focused on education, nutrition, and access to healthcare services, the research assesses changes in health outcomes among low-income families. The results demonstrate that community engagement and tailored interventions can significantly improve maternal and child health indicators, reducing disparities in health access and outcomes.